Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow

Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow

Ultrastructural Changes in Chloroplasts of Quercus rotundifolia Lam. in Response to Evernic Acid - ASCASO, C; RAPSCH, S (Annals of Botany, 1986)
The amount of total chlorophyll, chlorophylls a and b as well as the ratio of a to b decreased in chloroplasts isolated from Quercus rotundifolia leaves, kept for 17 d in a solution of 35.5 μM evernic acid in 1 mM Na HCO3, when compared with the chloroplasts of control leaves (kept in NaHCO3). The chloroplasts in the spongy parenchyma were smaller and the amount of starch and plastoglobuli lower. The number of grana per chloroplast section, the number of thylakoids per grana and the height of grana stacks were also less in the chloroplasts of leaves treated with evernic acid. Quantitative ultrastructural differences were determined by means of electron microscopy and image analysis techniques.
Keywords: chloroplasts; evernic acid; lichens; Quercus rotundifolia Lam.; ultrastructure